2020
DOI: 10.4018/978-1-7998-2128-1.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Financial Information

Abstract: The importance of corporate social responsibility (CSR) has been increasing especially in the last decade, due to the positive pressure exerted by society in general. This chapter analyses the relevance of CSR, associated theories and studies carried out in the last decade related to financial information and consequently accounting quality. The strong link between CSR and financial information that is directed towards knowledge of mitigation of asymmetry information is evident. We aim to contribute to the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In accordance with the legitimacy theory, companies share their social responsibility information with their stakeholders and legitimize their activities in this field (Gavancha and Sousa Paiva, 2020). CG can be a key to fill possible legitimacy gaps with more CSR disclosures (Mio et al , 2015).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In accordance with the legitimacy theory, companies share their social responsibility information with their stakeholders and legitimize their activities in this field (Gavancha and Sousa Paiva, 2020). CG can be a key to fill possible legitimacy gaps with more CSR disclosures (Mio et al , 2015).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Timely and relevant disclosure will help them in taking key decision during this crisis time. Legitimacy theory signifies that companies tend to report socially responsible information so that they can legitimize their behaviors to their stakeholder groups (Gavancha and Paiva, 2020). The legitimacy theory is used to describe social and environmental reports disclosure but it can be used in corporate report, suggested by Woodward et al (1996), as one possible legitimacy/accountability reporting framework, to communicate with the shareholders (Damaso and Lourenço, 2001).…”
Section: Legitimacy Theory and Accounting Disclosurementioning
confidence: 99%
“…Tsang (2001), Ogden and Clarke (2005) have explored corporate report behavior and concluded that organizations use such reporting for legitimacy purposes. It is theoretical stance that predicts companies' behavior toward managing and maintain the perspectives of key stakeholders though company disclosure (Gavancha and Paiva, 2020). Schiopoiu Burlea and Popa (2013) has identified role of legitimacy theory in explaining behavior of organization in providing voluntary disclosures in any jumpy economic environment condition like the COVID-19 pandemic.…”
Section: Legitimacy Theory and Accounting Disclosurementioning
confidence: 99%